(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to identify the effectiveness of using the constructive learning model in achievement and the productive tendency towards mathematics among second-grade intermediate students.The research sample was chosen randomly from Al-Istabraq Intermediate School for Girls, affiliated to the General Directorate of Education in Baghdad, Al-Rusafa /1, and it consisted of (40) female students from the second intermediate grade, by (20) students in each of the experimental and control research groups, and the two groups were rewarded with the following variables (Chronological age in months, intelligence, previous knowledge in mathematics, previous achievement, and the educational level of the parents). The experiment was applied in the first semester of the academic year (2021-2020) AD, and two research tools were prepared, namely: an achievement test in a subject Mathematics consists of (20) objective paragraphs of the multiple choice type, and by using the Keoder Richardson equation (KR-20), the value of the reliability coefficient was (0.86), and the measure of propensity produced towards mathematics is of (32) paragraphs, and by using the equation (Alpha-Cronbach) The reliability coefficient was (0.83, the two research tools were applied at the end of the experiment and after collecting the data and using the appropriate statistical means, the results showed the superiority of the experimental group students who studied using the constructive learning model in the achievement test and the measure of propensity produced towards a subject Mathematics is based on the control group students who studied in the usual way, and in light of the results, a number of recommendations and proposals were produced